PENGARUH FIRM SIZE, FINANCIAL DISTRESS, DEBT LEVEL, DAN MANAGERIAL OWNERSHIP TERHADAP KEPUTUSAN HEDGING PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Husna Anniyati; Hermanto Hermanto; Siti Aisyah Hidayati (JMM UNRAM - MASTER OF MANAGEMENT JOURNAL, 2020)
This study aims to analyze the influence of firm size, financial distress, debt level, and managerial ownership on hedging decisions on manufacturing companies listed on the Indonesia Stock Exchange. This type of research is associative-causality research. The population of this research is all the go pubic manufacturing companies on the Indonesia Stock Exchange, which are 170 companies. The number of samples used was 81 companies, which were taken using a purposive sampling method. Data collection techniques use documentation techniques obtained from the annual financial statements of manufacturing companies. The data analysis technique uses the logistic regression analysis method. The results of data analysis show that: (1) firm size and managerial ownership variables have a positive and significant effect on hedging decisions and (2) financial distress and debt levels have a negative and insignificant effect on hedging decisions.Keywords:hedging, firm size, financial distress, debt level, managerial ownership